Up close 2 : - Chamot, Anna Uhl (Thomson/Heinle, 2002)
Up Close is a four-level course which takes students from the elementary to the intermediates level, by providing clear and achievable goals in each unit and each level of series. It provides a graded, functional, grammatical, and lexical syllabus for students and teachers to work with.